THE EFFECTS VOCABULARY MASTERY AND THE READING SKILL TOWARDS STUDENTS WRITING ABILITY IN NARRATIVE TEXT - Maryamah Maryamah (Universitas Indraprasta PGRI, 2021)
Abstract: The aims of the research are to 1) The effects of vocabulary mastery and reading skills on students' writing ability in the narrative text at Private Junior High Schools in Rangkasbitung. 2) The effect of vocabulary mastery towards students writing ability in the narrative text at Private Junior High Schools in Rangkasbitung. 3) The research findings are: 1) There are any significant effects of vocabulary mastery and reading skill jointly towards students writing ability in the narrative text at Private Junior High Schools in Rangkasbitung. That is proved by sig. value = 0.000 < 0.05. and F0 = 25.833. 2) There is a significant effect of the vocabulary mastery towards students writing ability in the narrative text at Private Junior High Schools in Rangkasbitung. That is proved by sig – 0.000 < 0.05 and to = 4.948. 3) That is proved by sig. value = 0.000 < 0.05. and t0 = 4.948. 3) Keywords: Vocabulary mastery, reading skill, narrative writing text.